METHODS TO STUDY THE PVY POPULATION IN THE POTATO - Yin, Zhimin (Plant Breeding and Seed Science, 2017)
The PVY population in the potato has been studied continuously using tobacco bait plants in potato fields at Młochów since 1980 at two-year intervals and in potato tuber samples collected from different regions of Poland since 2001 yearly. The paper presents the combined biological, serological and molecular assays for PVY identification and strain classification. Biologically, PVY strains are defined with respect to their ability to elicit hypersensitive resistance (HR) mediated by N genes in differential potato cultivars (King Edward, Desiree and Pentland Ivory) and to symptoms in the tobacco (cultivar Samsun). Serologically, an ELISA assay based on polyclonal or monoclonal cocktail antibodies recognizes all PVY strain types, while the specif-ic monoclonal antibodies help to recognize PVYN or PVYO/PVYC strains. Multiplex RT-PCR, Real-time RT-qPCR and sequencing-based assays are used to define the PVY genome structure. In the Polish population of PVY, the strains PVYO, PVYNTN, PVYN-Wi, PVYZ-NTN and PVYE were identified, while the PVYC strain was not detected.